Patterns of Middle-Class Communities Adaptation to the Village SDGS Program in Bogor Regency - Nur Meily Isnaeni; Moh Dulkiah; Asep Dadan Wildan (TEMALI : Jurnal Pembangunan Sosial, 2022)
Village is the smallest territorial space in Indonesia with a complex socio-economic problem. For this reason, the village SDGs was born as a micro-based global development agenda expected to realize village development efficiently. This program has the main objective of “No One Left Behind” with 18 main objectives that cover all levels of society. Among the best ideas in the 18 goals, the conclusion is still focused on sustainable village development through eradicating lower-class social issues with upper-class support. Then the question arises, "What is the role of the middle class, and how do they adapt to these 18 goals?". This study uses a mixed explanatory design method and quantitative and qualitative methods. The phenomena that occur are studied and analyzed through sequential techniques to conclude that the adaptation pattern of the middle-class community is distinguished based on their response to the village SDGs program.